Fatigue and Exercise Intolerance as Initial Manifestations of a Nonsyndromic Mitochondrial Disorder Due to the Variant m.3243A>G - Josef Finsterer; Sinda Zarrouk (Case Reports in Neurological Medicine)
Objectives. Fatigue and exercise intolerance have been only rarely reported as initial- and sole-onset manifestations of a mitochondrial disorder (MID). We present a patient with nonsyndromic MID with fatigue and exercise intolerance as its initial manifestations of the disease. Case Report. A 39 yo female experienced fatigue since age 18 and exercise intolerance since age 21. Later on, she developed Hashimoto thyroiditis, recurrent diffuse headache, and double vision upon exercise. Clinical exam revealed short stature, bilateral ptosis, partially reduced tendon reflexes, and hypertrophic calves. Serum lactate was elevated, and the lactate stress test was abnormal. Workup for suspected MID revealed ragged-red fibers and NADH-deficient muscle fibers, and biochemical investigations revealed a mild complex-I defect. mtDNA sequencing revealed the variant m.3243A>G with a heteroplasmy rate of 70% in the muscle. Conclusions. This case shows that the initial manifestation of a MID can be fatigue and exercise intolerance. MIDs due to the m.3243A>G variant may have a slowly progressive course and only delayed multisystem involvement. The variant m.3243A>G may not only manifest as syndromic MID, particularly MELAS but also as nonsyndromic phenotype. MIDs should be considered as differentials of chronic fatigue even if no other phenotypic manifestation of a MID is present.